Contest Corner: Developing Mathematical Thinking (pp. 51--54) - Flick, Michael; Kuchey, Debora (Ohio Journal of School Mathematics, 2020)
This Contest Corner Column discusses a generalized problem that provides a challenge to most students and reinforces concepts useful to developing the kind of thinking needed to excel in mathematics competition.